Is it true there was a cisgender-heterosexual-military dictatorship in Brazil? - Afonso-Rocha, Rick (2021)
Renan Quinalha was the first to use the expression “heterosexual-military dictatorship” to describe theheterogeneity of sexual (and gender) policies adopted, or at least intensified, during the Brazilian military dictatorship. Sincedefending his PhD dissertation in 2017, Quinalha became the main national reference in studies on “homosexualities” anddictatorship, resulting in the popularized use of the term, both in academia and political activism. In this study, I explore thetheoretical-epistemological (im)pertinences of such concept.